The famous five (five on a treasure island) - Blyton, Enid (London, Hodder Children's Books, 1997)
CLASSIC FICTION (CHILDREN'S / TEENAGE). Meet Julian, Dick, Anne, George and Timothy. Together they are THE FAMOUS FIVE - Enid Blyton's most popular adventure series. 'There was something else out on the sea by the rocks - something dark that seemed to lurch out of the waves ...What could it be?' Julian, Dick and Anne are spending the holidays with their tomboy cousin George and her dog, Timothy. One day, George takes them to explore nearby Kirrin Island, with its rocky little coast and old ruined castle on the top. Over on the island, they make a thrilling discovery, which leads them deep into the dungeons of Kirrin Castle on a dangerous adventure. Who - and what - will they find there? This edition features the text from the Classic edition and contains the original cover art and inside drawings by Eileen Soper. Ages 9+